Correction to: Vitamin D deficiency and risk of cardiovascular diseases: a narrative review - Babikir Kheiri; Ahmed Abdalla; Mohammed Osman; Sahar Ahmed; Mustafa Hassan; Ghassan Bachuwa (BMC, 2018)
In the original publication of this article [1], the reference number [42] under the section 'vitamin D and Cardiovascular diseases' (page no.2) should be [37].